2010
DOI: 10.1002/jbmr.237
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intravenous and intramuscular neridronate regimens for the treatment of paget disease of bone

Abstract: Aminobisphosphonates actually represent the most common treatment for Paget disease of bone (PDB). In a previous study we demonstrated that either zoledronic acid (4 mg) or neridronate (200 mg) given as a single intravenous infusion showed a similar shortterm efficacy in achieving biochemical remission in up to 90% of patient nonresponders to pamidronate. In this study we compared the long-term (36 months) effects of a same neridronate dose (200 mg) given as an intravenous (100-mg infusion for 2 consecutive da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The symptoms usually appear 24 to 36 hours after the first administration, mainly in previously untreated patients, and persist for less than 36 hours. 24,27,29,31,43 Other reported adverse events include headache, diarrhoea, and dermatitis. 30 No cases of jaw osteonecrosis have been reported in patients treated with neridronate, even after longer periods of treatment.…”
Section: Safetymentioning
confidence: 99%
“…The symptoms usually appear 24 to 36 hours after the first administration, mainly in previously untreated patients, and persist for less than 36 hours. 24,27,29,31,43 Other reported adverse events include headache, diarrhoea, and dermatitis. 30 No cases of jaw osteonecrosis have been reported in patients treated with neridronate, even after longer periods of treatment.…”
Section: Safetymentioning
confidence: 99%
“…On the basis of the results obtained in this study, the authors consequently performed a randomized open-label study evaluating the long-term efficacy of the same neridronate dose (200 mg), either administered as an intravenous or intramuscular regimen, in 56 patients with PDB, with a 3-year follow-up 28. After 6 months, 92.6% of patients receiving intravenous neridronate and 96.5% of patients with intramuscular regimen achieved a therapeutic response in terms of normalization of alkaline phosphatase levels or reduction of at least 75% in total alkaline phosphatase excess (Figure 2).…”
Section: Clinical Use Of Neridronatementioning
confidence: 99%
“…Even though its potency is lower than zoledronic acid, in a recent comparative study, this compound, given as intravenous 100 mg infusion for 2 consecutive days, was as effective as zoledronic acid in achieving a therapeutic response at 6 months in > 90% of patients non-responders to pamidronate treatment [96]. A subsequent study confirmed the efficacy of a single neridronate course (100 mg for 2 consecutive days), with remission rates in 93 and 90% of patients at 6 and 12 months, respectively [97]. In contrast to what observed with zoledronic acid, a progressive decrease in response rates was observed after 1 year from infusion of neridronate, and therapeutic response at 36 months was maintained in 48% of PDB cases.…”
Section: Cmentioning
confidence: 74%
“…In contrast to what observed with zoledronic acid, a progressive decrease in response rates was observed after 1 year from infusion of neridronate, and therapeutic response at 36 months was maintained in 48% of PDB cases. Of interest, the same study demonstrated a comparable efficacy at all time points of a same cumulative neridronate dose (200 mg) given as intramuscular regimen (25 mg injection weekly for 2 months) [97]. This might be of particular value for patients intolerant to oral bisphosphonates and unwilling or unable to undergo intravenous infusions.…”
Section: Cmentioning
confidence: 92%